Programma: 12 december: Andrew Strong; 26 december: Gala v/h Nederlandse lied; 29 december: The Scene; 30 december: Hallo Venray (1993)
Programma: 12 december: Andrew Strong; 26 december: Gala v/h Nederlandse lied; 29 december: The Scene; 30 december: Hallo Venray.